Brand and generic use of inhalation medication and frequency of switching in children and adults: A population-based cohort study. (3rd October 2018) - Engelkes, Marjolein; van Blijderveen, Jan C.; Overbeek, Jetty A.; Kuiper, Josephine; Herings, Ron C. M.; Sturkenboom, Miriam C. J. M.; de Jongste, Johan C.; Verhamme, Katia M. C.; Janssens, Hettie M.
ABSTRACT: Background : The expiration of patents of brand inhalation medications and the ongoing pressure on healthcare budgets resulted in a growing market for generics. Aim : To study the use of brand and generic inhalation medication and the frequency of switching between brand and generic and between devices. In addition, we investigated whether switching affected adherence. Methods : From dispensing data from the Dutch PHARMO Database Network a cohort aged ≥ 5 years, using ≥ 1 year of inhalation medication between 2003 and 2012 was selected. Switching was defined as changing from brand to generic or vice versa. In addition, we studied change in aerosol delivery device type (e.g., DPI, pMDI, and nebulizers). Adherence was calculated using the medication possession ratio (MPR). Results : The total cohort comprised 70, 053 patients with 1, 604, 488 dispensations. Per calendar year, 5% switched between brand and generic inhalation medication and 5% switched between devices. Median MPRs over the first 12 months ranged between 33 and 55%. Median MPR over the total period was lower after switch from brand to generic and vice versa for formoterol (44.5 vs. 42.1 and 63.5 vs. 53.8) and beclomethasone (93.8 vs. 59.8 and 81.3 vs. 55.9). Conclusion : Per year, switching between brand and generic inhalation medication was limited to 5% of the patients, switching between device types was observed in 5% as well. Adherence to both generic and brand inhalation medication was low. Effect of switching on adherence was contradictory; depending on time period, medication and type, and direction of switching. Further research on reasons for switching and potential impact on clinical outcomes is warranted.